Catalytic Activity of Water-Soluble Palladium Nanoparticles with Anionic and Cationic Capping Ligands for Reduction, Oxidation, and C-C Coupling Reactions in Water - Jan W. Farag; Ragaa Khalil; Edwin Avila; Young-Seok Shon (Nanomaterials)
The availability of water-soluble nanoparticles allows catalytic reactions to occur in highly desirable green environments. The catalytic activity and selectivity of water-soluble palladium nanoparticles capped with 6-(carboxylate)hexanethiolate (C6-PdNP) and 5-(trimethylammonio)pentanethiolate (C5-PdNP) were investigated for the reduction of 4-nitrophenol, the oxidation of α,β-conjugated aldehydes, and the C-C coupling of phenylboronic acid. The study showed that between the two PdNPs, C6-PdNP exhibits better catalytic activity for the reduction of 4-nitrophenol to 4-aminophenol in the presence of sodium borohydride and the selective oxidation of conjugated aldehydes to conjugated carboxylic acids. For the latter reaction, molecular hydrogen (H2) and H2O act as oxidants for the surface palladium atoms on PdNPs and conjugated aldehyde substrates, respectively. The results indicated that the competing addition activities of Pd-H and H2O toward the π-bond of different unsaturated substrates promote either reduction or oxidation reactions under mild conditions in organic solvent-free environments. In comparison, C5-PdNP exhibited higher catalytic activity for the C-C coupling of phenylboronic acid. Gas chromatography–mass spectrometry (GC-MS) was mainly used as an analytical technique to examine the products of catalytic reactions.